Warunki utrzymania i poprawy konkurencyjności polskich przedsiębiorstw na wspólnym rynku europejskim - Wysocki, Jacek (Support and Improvement of Competitiveness of Polish Companies on the Common European Market, 2008)
In principle it turns out that the success of Polish companies on the common European market depends on their ability to adapt to new conditions of competition. In practice this aim can be achieved by initiating suitable adapting and restructuring programmes which allow to eliminate weak-nesses of Polish companies, such as: poor quality of products, lack of capital, low level of investments, outdated technologies, insufficient management and marketing knowledge or inexperience. Apart from that, in order to compete with foreign enterprises, Polish companies should not only concentrate on profits, but first of all on the growth of the firm value and on the creation of the value for potential clients. (original abstract) At present economic situation, Polish companies should throw away traditional, related with costs, sources of a competitive advantage and build their long-term strategies on the base of direct sources of competitive advantage, coming from their internal resources and competences. In fact, only internal sources give an enterprise a permanent competitive advantage that allows to compete with foreign companies and determines its market success.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 444-454